Slow conduction in mixed cultured strands of primary ventricular cells and stem cell-derived cardiomyocytes - Kucera, Jan Pavel; Prudat, Yann; Marcu, Irene; Azzarito, Michela; Ullrich, Nina D. (Frontiers in cell and developmental biology, 2015)
Modern concepts for the treatment of myocardial diseases focus on novel cell therapeutic strategies involving stem cell-derived cardiomyocytes (SCMs). However, functional integration of SCMs requires similar electrophysiological properties as primary cardiomyocytes (PCMs) and the ability to establish intercellular connections with host myocytes in order to contribute to the electrical and mechanical activity of the heart. The aim of this project was to investigate the properties of cardiac conduction in a co-culture approach using SCMs and PCMs in cultured cell strands.